2019
DOI: 10.1002/brb3.1422
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the multiple sclerosis diagnosis in the Norwegian Patient Registry

Abstract: BackgroundHealth registries may yield important data for epidemiological studies. However, in order to be a valuable source for information, the registered data have to be correct.ObjectivesThe aim of the study was to validate data from the Norwegian Patient Registry (NPR) regarding multiple sclerosis (MS).Materials and MethodsWe obtained data on individuals residing in Nordland County and registered with a MS diagnosis in the NPR or in local hospital records. The NPR data included a unique 11‐digit personal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The MS diagnosis in NPR has previously been validated, with a sensitivity of 97% and positive predictive value 0.92. 16 MS diagnoses registered in NPR, but not in the MSR, were validated with information from hospital records using the 2017 diagnostic criteria for MS. 17 …”
Section: Methodsmentioning
confidence: 99%
“…The MS diagnosis in NPR has previously been validated, with a sensitivity of 97% and positive predictive value 0.92. 16 MS diagnoses registered in NPR, but not in the MSR, were validated with information from hospital records using the 2017 diagnostic criteria for MS. 17 …”
Section: Methodsmentioning
confidence: 99%
“…Diagnosis of MS is a prolonged and challenging process and some patients could be misdiagnosed [26]. However, a recent validation study on individuals residing in Nordland County in Norway and registered with MS in NPR examined the medical record of these individuals and reported that 91.5% of patients had a confirmed MS diagnosis [27]. We believe that our inclusion criteria for MS patients (patients with at least two registered diagnoses in specialist care or combination of information on diagnoses in specialist care with information on use of MS medications) provided a highly reliable identification of MS patients.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…To assess the completeness of the cohort, we will link data from the Norwegian Patient Registry and compare the number of incident patients in this registry within the corresponding geographical area and inclusion years, with the number of included patients. Validation of correct diagnoses in the Norwegian Patient Registry has been performed with other diagnoses [21], but not within IBD. However, a Swedish study found high validity of IBD diagnoses within the Swedish Patient Registry [22].…”
Section: Discussionmentioning
confidence: 99%